Antibiotic free dehydrated Human Amnion membrane from C-section deliveries to accelerate wound healing - et al., P. Raghu Babu (International Journal of Advanced Science and Technology, 2019)
The human amniotic membrane (HAM) or amnion has been used as a graft for surgical procedures due to its non-immunogenic property. Antibiotic free preparation of dehydrated human amnion membrane from Caesarean (C-section) deliveries was achieved to prevent the modification/changes in cell functionality and differentiation of amnion intact cells. Separation of amnion from chorian manually and by treating with 12% sodium chloride for 30 minutes. Amnion was then washed with 0.9% normal saline before it was placed in a hot air oven at 40 C for 2 hours for drying. Gamma sterilization was done with 25Kgy dose with amnion membrane packed in tyvek pouch. Histological studies revealed an intact epithelial layer with amnion that could enhance wound healing faster compared to decellularised amnion membrane due to its naïve nature and intact growth factors. Dehydrated human amnion membrane (dHAM) had good tensile strength (1.649 N) and elasticity (Elongation -13.7 %) accounting to the presence of elastin protein, that transports key growth factors for wound healing.